simply the above question
Attachments:
![](https://hi-static.z-dn.net/files/d24/18f2c5c0be16145d25b07b592426eab0.jpg)
Answers
Answered by
5
HY THERE.........................
(-5) CUBE +(-12) CUBE (17) CUBE = -125 -1728 +4913 = 3060
THE REQ ANS IS 3060 ......................................
;)
(-5) CUBE +(-12) CUBE (17) CUBE = -125 -1728 +4913 = 3060
THE REQ ANS IS 3060 ......................................
;)
rkkumarrohit09p9mnrr:
Since [(-5)+(-12)+17]=0; So, [(-5)³+(-12)³+17³]= 3×(-5)×(-12)×17=3060
Answered by
2
hey..
(-125) + (-1728) + 4913
-125 - 1728 + 4913.........( because + × - is -)
-1853 + 4913
=. -3060
hope you like
(-125) + (-1728) + 4913
-125 - 1728 + 4913.........( because + × - is -)
-1853 + 4913
=. -3060
hope you like
Similar questions